A high potential optical method for sensitive and selective detection of essential elements - Yap, Wing Fen; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Saleviter, Silvan; Zainudin, Afiq Azri; Sheh Omar, Nur Alia (2018)
An optical sensor based on surface plasmon resonance (SPR) phenomenon has been emerged for sensing a variety of analytes, including essential elements. It has numerous advantages, which include very high sensitivity, simple sample preparation, low cost, fast measurement capability, no requirement for reference solution, high reproducibility, ability to monitor kinetic behaviour, label-free detection, and nondestructive. The instrument and different developments on active layers or recognition molecules for sensitivity and selectivity improvements were explored. Further investigation in SPR optical sensor technology will expand SPR detection abilities and allow SPR sensing to be used widely including in environmental monitoring as an effective essential elements sensor in the future.